Alterations in long noncoding RNAs in women with and without polycystic ovarian syndrome. (1st October 2019) - Butler, Alexandra E.; Hayat, Shahina; Dargham, Soha R.; Malek, Joel A.; Abdulla, Silvana A.; Mohamoud, Yasmin A.; Suhre, Karsten; Sathyapalan, Thozhukat; Atkin, Stephen L.
Abstract: Long noncoding RNAs (lncRNAs) are RNA transcripts over 200 nucleotides long that are not translated into protein; however, there is increasing evidence of their regulatory functions. To date, there are few studies measuring lncRNA in control women or women with polycystic ovary syndrome (PCOS). Objective: To determine lncRNA differences between PCOS and control women. Design: Cross sectional study. Patients: Twenty four anovulatory women with all three diagnostic features of PCOS compared to 24 control women in the follicular phase of their menstrual cycle from a PCOS biobank. Results: Women with PCOS were age and weight matched compared to the control women but were significantly insulin resistant and hyperandrogenemic ( P  < .01). Eight lncRNA ( P  < .05) were detected that differed between PCOS and control women, but only MIRLET7BHG correlated with body mass index ( r  = .66, P  < .05). No lncRNA correlated with antimullerian hormone (AMH) levels, insulin resistance (HOMA‐IR) or the free androgen index (FAI). Ingenuity pathway assessment (IPA) did not identify any functional pathways for the lncRNAs. Conclusion: LncRNAs differ between anovulatory PCOS and control women in the follicular phase of the menstrual cycle. It is unclear if this is due to inherent differences between PCOS and control women or due to changes in lncRNA that are menstrual cycle dependent. However, their IPA did not identify linked pathways, likely because few functions are as yet assigned to these lncRNAs.